To save humanity from hell : what matters most for a healthy future - Frenk, Julio; Hoffman, Steven (Steven J.) (Oxford University Press, 2015)
"To Save Humanity from Hell" is a collection of short, honest essays on what single issue matters most for the future of global health. Authored by the world's leading voices from science, politics, and social advocacy, this collection is both a primer on the major issues of our time and a potential blueprint for post-2015 health and development. This unparalleled collection will provide illuminating and thought-provoking reading for anyone invested in our collective future and well-being"--Provided by publisher.